Does Motor Training of the Nonparetic Side Influences Balance and Function in Chronic Stroke? A Pilot RCT - Shanta Pandian; Kamal Narayan Arya; Dharmendra Kumar (The Scientific World Journal)
Background. Balance and functional abilities are controlled by both sides of the body. The role of nonparetic side has never been explored for such skills. Objective. The objective of the present study was to examine the effect of a motor therapy program primarily involving the nonparetic side on balance and function in chronic stroke. Method. A randomized controlled, double blinded trial was conducted on 39 poststroke hemiparetic subjects (21, men; mean age, 42 years; mean poststroke duration, 13 months). They were randomly divided into the experimental group (n=20) and control group (n=19). The participants received either motor therapy focusing on the nonparetic side along with the conventional program or conventional program alone for 8 weeks (3 session/week, 60 minutes each). The balance ability was assessed using Berg Balance Scale (BBS) and Functional Reach Test (FRT) while the functional performance was measured by Barthel Index (BI). Result. After intervention, the experimental group exhibited significant (P<0.05) change on BBS (5.65 versus 2.52) and BI (12.75 versus 2.16) scores in comparison to the control group. Conclusion. The motor therapy program incorporating the nonparetic side along with the affected side was found to be effective in enhancing balance and function in stroke.